{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

lect15

# lect15 - HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES...

This preview shows pages 1–5. Sign up to view the full content.

HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES Outline HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES CAUCHY DISTRIBUTIONS MANY-TO-ONE TRANSFORMATIONS 1 / 13 Xinghua Zheng Lect 15: Hazard functions; Transformation of variables

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES EXPONENTIAL RANDOM VARIABLES Suppose N ( t ) is a Poisson process with rate λ . Let T = T 1 be the waiting time for the first event. Then T has F T ( t ) = P [ T t ] = P [ N ( t ) 1 ] = 1 - exp ( - λ t ) , f T ( t ) = F 0 T ( t ) = λ exp ( - λ t ) . T is said to have an exponential distribution with (rate) parameter λ . 2 / 13 Xinghua Zheng Lect 15: Hazard functions; Transformation of variables
HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES HAZARD FUNCTIONS Let T be a nonnegative continuous random variable with density f and cdf F . Think of T as the lifetime of some item. The ratio of the chance that the item dies in the next dt time units, given that it has lived at least t time units to dt is λ ( t ) = P [ t < T t + dt | T > t ] dt = P [ t < T t + dt ] dt P [ T > t ] = f ( t ) dt dt ( 1 - F ( t )) = - d dt ( log ( 1 - F ( t ))) . λ ( t ) is called the death rate , or failure rate , or hazard rate at time t . S ( t ) := P [ T > t ] = 1 - F ( t ) is called the survival probability at time t . Example: If T has an exponential distribution with parameter λ , then λ ( t ) = . 3 / 13 Xinghua Zheng Lect 15: Hazard functions; Transformation of variables

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
HAZARD FUNCTIONS TRANSFORMATION OF VARIABLES HAZARD FUNCTIONS, ctd In general, if you know the hazard function λ ( t ) of T , what can you say about the distribution of T ? λ ( t ) = - d dt ( log ( 1 - F ( t ))) R t 0 λ ( s ) ds = . S ( t ) = 1 - F ( t ) = exp ( - R t 0 λ ( s ) ds ) f ( t ) = - d dt S ( t ) = λ ( t ) exp ( - R t 0 λ ( s ) ds ) Example: If T has the memoryless property with density f ( t ) , then λ ( t ) = for all t 0, so T .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern